Using a private space for prayer in the inner space of the dwelling, By utilizing the design ideas borrowed from the Islamic identity - Abdulrahman, Ranyh Ali Ahmad (Journal of Humanities & Social Sciences, 2021)
This research aims to design a private space as a chapel in the inner space of a limited-space housing to achieve the privacy and comfort possible for its users that meets the functional requirements that help in reverence and not the space that calls for breath and being preoccupied with worship, then identifying the elements that can be used in the design of this space and how Its integration with the contemporary building design in a way that is commensurate with the economic, environmental and social constituents of those who live in the house. The importance lies in the following put forward a new idea that can contribute to achieving psychological comfort for the housing users In the dwelling it gives the psychological comfort to the worshiper, as it can be used as a place that helps to teach children to pray, or gathering to read the Qur’an, and a visitor who does not pray may see it in his heart and pray in his heart, and in it the Muslim can pray supererogatory prayers, and pray the night, and pray the woman, as well as the man If it is not possible to go to the whole mosque. The researcher used the descriptive method to study the elements that can be employed in designing the area under study and reached the most important results that allocating an area for prayer inside the residential space contributes greatly to achieving the benefit of privacy and psychological calm and also can benefit from the employment of some simple decorative elements to define the area of ​​the prayer area in keeping with the modern home décor. The most important recommendations of the research consisted in making use of design thinking and elements of Islamic identity by re-employing them with an innovative vision in line with modern designs of contemporary housing. It is necessary to think with an innovative vision to solve design problems and make the most of available spaces and employ them using the principle of flexibility to achieve the needs of users.